1973
DOI: 10.1136/bmj.3.5877.423
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension in Tetanus

Abstract: SummaryThree patients with severe tetanus had episodes of profound arterial hypotension lasting from minutes to hours. The blood pressure was recorded continuously for 13, 19, and six days respectively by an intra-arterial catheter, and other measurements Included heart rate, central venous pressure, cardiac output, and blood gases.The hypotension was distinguished from that of "shock", for there was no clinical evidence of peripheral vasoconstriction and no tachycardia. It could not be attributed to disturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Inotropes are required for the treatment of various complications in patients with severe tetanus—autonomic instability, septic shock, and myocarditis. 9 17 18 These factors, in turn, are associated with increased mortality. Angurana et al too found inotrope use to be associated with mortality in tetanus ( p -value of 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Inotropes are required for the treatment of various complications in patients with severe tetanus—autonomic instability, septic shock, and myocarditis. 9 17 18 These factors, in turn, are associated with increased mortality. Angurana et al too found inotrope use to be associated with mortality in tetanus ( p -value of 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, episodes of profound hypotension lasting from minutes to hours without tachycardia were observed by Corbett et al [13]. The onset and end of such episodes was often abrupt and the hypotension was often produced in response to a stim-ulus.…”
Section: Cardiovascular Disturbancesmentioning
confidence: 94%
“…The onset and end of such episodes was often abrupt and the hypotension was often produced in response to a stim-ulus. The hypotension was not due to sustained sympathetic nervous overactivity, since small doses of noradrenaline produced a rise in blood pressure and heart rate in these patients, but may represent another effect of tetanus on autonomic nervous activity including impairment of baroreceptor reflexes [13]. A further patient who developed a phase of hypotension when sympathetic activity appeared minimal was described by Kerr et al [30].…”
Section: Cardiovascular Disturbancesmentioning
confidence: 95%